2018
DOI: 10.1007/s00249-018-1281-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution between chemistry and biology

Abstract: Biological evolution is reduced to three fundamental processes in the spirit of a minimal model: (i) Competition caused by differential fitness, (ii) cooperation of competitors in the sense of symbiosis, and (iii) variation introduced by mutation understood as error-prone reproduction. The three combinations of two fundamental processes each, () competition and mutation, () cooperation and competition, and () cooperation and mutation, are analyzed. Changes in population dynamics that are induced by bifurcation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 106 publications
(140 reference statements)
0
1
0
Order By: Relevance
“…Through the closed clamp structure, IFIT5 can specifically bind to the negatively charged virus 5'-pppRNA and change the virus RNA sequence, thus inhibiting the replication of virus RNA (Abbas et al 2013). Previous studies have shown that the extremely conservative sites of the receptor recognize the invariant residues of the ligand, while the ligand residues recognized by the positive selection site are variable (Daugherty and Malik 2012;Schuster 2018). This indicates that the immune function of IFIT5 protein is affected by both conserved domain and virus selection pressure.…”
Section: Discussionmentioning
confidence: 97%
“…Through the closed clamp structure, IFIT5 can specifically bind to the negatively charged virus 5'-pppRNA and change the virus RNA sequence, thus inhibiting the replication of virus RNA (Abbas et al 2013). Previous studies have shown that the extremely conservative sites of the receptor recognize the invariant residues of the ligand, while the ligand residues recognized by the positive selection site are variable (Daugherty and Malik 2012;Schuster 2018). This indicates that the immune function of IFIT5 protein is affected by both conserved domain and virus selection pressure.…”
Section: Discussionmentioning
confidence: 97%